2023
DOI: 10.1021/acssuschemeng.3c01469
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Loop Recycling of Polyols from Thermoset Polyurethanes by tert-Amyl Alcohol-Mediated Depolymerization of Flexible Foams

Martin B. Johansen,
Bjarke S. Donslund,
Erik Larsen
et al.

Abstract: The production of thermoset materials makes up 12% of global plastic production. With increasing demands for plastics and with emphasis on the legacy burden of thermoset polymers, new solutions are indispensable to shift our society from the current linear make–use–dispose mindset to a scenario where materials are utilized in a more circular fashion. In 2020, the production of polyurethane (PU) reached approx. 24 million tons, making it the sixth most produced polymer. However, the inherent stability of PU ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Our previous endeavours on depolymerisation of PU materials revealed tert -amyl alcohol with catalytic amounts of KOH as an efficient solvolysis medium. 44,45 In those studies, we demonstrated the general value of the depolymerisation process for flexible foam-, rigid foam-, flexible solid- and rigid solid polyurethanes. Herein, we disclose our efforts to disassemble elastane by this process initially starting from virgin elastane, moving to elastane recovered by dissolution and finally directly from textile blends to assess the possibility of recovering the main textile component and isolating monomers suitable for repolymerization of elastane (Scheme 1b, bottom).…”
Section: Introductionmentioning
confidence: 69%
“…Our previous endeavours on depolymerisation of PU materials revealed tert -amyl alcohol with catalytic amounts of KOH as an efficient solvolysis medium. 44,45 In those studies, we demonstrated the general value of the depolymerisation process for flexible foam-, rigid foam-, flexible solid- and rigid solid polyurethanes. Herein, we disclose our efforts to disassemble elastane by this process initially starting from virgin elastane, moving to elastane recovered by dissolution and finally directly from textile blends to assess the possibility of recovering the main textile component and isolating monomers suitable for repolymerization of elastane (Scheme 1b, bottom).…”
Section: Introductionmentioning
confidence: 69%
“…Products isolated from this additional treatment were significantly lighter in color than the original hydrolyzed repolyol. While most literature concerning acidolysis focuses on the recovery of the polyol component of PUF, TDA obtained after hydrolysis could be a valuable coproduct from PUF acidolysis. , Toluene diisocyanate (TDI), a precursor to PUF, is synthesized by reacting TDA with phosgene; if the TDA component of PUF can be isolated, it can be useful in the creation of new PUF materials as well. , In our approach, a total of around 80 wt % of the input PUF can be recovered as repolyol (66–68 wt %) and TDA (12–13 wt %) for use in making new PU materials. Additionally, excess MA from acidolysis was neutralized to MA disodium salt after workup, which allows for the input MA to be recovered and recycled by reacidification.…”
Section: Discussionmentioning
confidence: 99%
“…High yields of toluenediamine (>95%), a diisocyanate precursor, and polyols were recovered . In a further work, they showed that the recycled polyol could 100% substitute virgin polyol in PU synthesis, while maintaining good mechanical performance (e.g., virgin PU tensile strength = 93 kPa, and recycled PU tensile strength = 96 kPa) . Zhao and Semetey investigated the methanolysis of PUs using a range of basic catalysts (DBU, TBD, tert -butoxide) .…”
Section: Polyurethanesmentioning
confidence: 99%